Outcome Accuracy of the Emergency Medical Dispatcher's Initial Selection of a Diabetic Problems Protocol. Issue 1 (10th December 2013) - Clawson, Jeff; Scott, Greg; Lloyd, Weston; Patterson, Brett; Barron, Tracey; Gardett, Isabel; Olola, Christopher
Abstract Introduction Diabetes mellitus, although a chronic disease, also can cause acute, sudden symptoms requiring emergency intervention. In these cases, Emergency Medical Dispatchers (EMDs) must identify true diabetic complaints in order to determine the correct care. In 911 systems utilizing the Medical Priority Dispatch System (MPDS), International Academies of Emergency Dispatch-certified EMDs determine a patient's chief complaint by matching the caller's response to an initial pre-scripted question to one of 37 possible chief complaints protocols. The ability of EMDs to identify true diabetic-triggered events reported through 911 has not been studied. Objective The primary objective of this study was to determine the percentage of EMD-recorded patient cases (using the Diabetic Problems protocol in the MPDS) that were confirmed by either attending paramedics or the hospital as experiencing a diabetic-triggered event. Methods This was a retrospective study involving six hospitals, one fire department, and one ambulance service in Salt Lake City, Utah USA. Dispatch data for one year recorded under the Diabetic Problems protocol, along with the associated paramedic and hospital outcome data, were reviewed/analyzed. The outcome measures were: the percentage of cases that had diabetic history, percentage of EMD-identified diabetic problems cases that were confirmed by Emergency Medical Services (EMS) and/or hospital records as true diabetic-triggered events, and percentage of EMD-identified diabetic patients who also had other medical conditions. A diabetic-triggered event was defined as one in which the patient's emergency was directly caused by diabetes or its medical management. Descriptive statistics were used for categorical measures and parametric statistical methods assessed the differences between study groups, for continuous measures. Results Three-hundred ninety-three patient cases were assigned to the Diabetic Problems Chief Complaint protocol. Of the 367 (93.4%) patients who had a documented history of diabetes, 279 (76%) were determined to have had a diabetic-triggered event. However, only 12 (3.6%) initially assigned to this protocol did not have a confirmed history of diabetes. Conclusions Using the MPDS to select the Diabetic Problems Chief Complaint protocol, the EMDs correctly identified a true diabetic-triggered event the majority of the time. However, many patients had other medical conditions, which complicated the initial classification of true diabetic-triggered events. Future studies should examine the associations between the five specific Diabetic Problems Chief Complaint protocol determinant codes (triage priority levels) and severity measures, eg, blood sugar level and Glasgow Coma Score. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>J</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Clawson</surname> </string-name>, <string-name><given-names>G</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Scott</surname></string-name>, <string-name><given-names>W</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Lloyd</surname></string-name>, <string-name><given-names>B</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Patterson</surname></string-name>, <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Barron</surname></string-name>, <string-name><given-names>I</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Gardett</surname></string-name>, <string-name><given-names>C</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Olola</surname></string-name>. Outcome accuracy of the Emergency Medical Dispatcher's initial selection of a Diabetic Problems Protocol . <source>Prehosp Disaster Med</source>. <year>2013</year>:<volume>28</volume>(<issue>6</issue>):<fpage>1</fpage>-<lpage>6</lpage></mixed-citation>.